2020
DOI: 10.1590/s1519-994020210732020
|View full text |Cite
|
Sign up to set email alerts
|

Quality of meat from Santa Ines sheep with different biotypes and slaughtering weights

Abstract: The Santa Inês breed is of great importance for the lamb production chain in Brazil. The adaptive and reproductive characteristics of this breed favor its use in future breeding programs for the production of sheep for slaughter in northeastern Brazil. This study evaluated the carcass characteristics, physical parameters, chemical composition and determination of the fatty acid profile of the lambs of the traditional and modern biotypes, slaughtered at 32 kg and 34 kg. Thirty-six Santa Inês lambs were used, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
0
0
1
Order By: Relevance
“…Ewe sheep fed more energy-dense diets had increased values of ethereal extract in their meat. According to Gois et al (2017) andOliveira et al (2020), the mean value for this variable was 3% to 3.75% in the meat of confined lambs. Araújo et al (2014) compared animals on pasture with and without supplementation and observed higher lipid values in the meat of supplemented animals, with values of 3.67% and 2.02%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ewe sheep fed more energy-dense diets had increased values of ethereal extract in their meat. According to Gois et al (2017) andOliveira et al (2020), the mean value for this variable was 3% to 3.75% in the meat of confined lambs. Araújo et al (2014) compared animals on pasture with and without supplementation and observed higher lipid values in the meat of supplemented animals, with values of 3.67% and 2.02%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Neste sentido, é importante destacar que o manejo adequado da matéria orgânica do solo (MOS) aumenta a retenção de água, disponibiliza nutrientes e favorece o desenvolvimento de microrganismos benéficos às plantas (RASUL et al, 2022), sendo benéfico para o feijão-caupi, principalmente sob restrição hídrica (THAPA et al, 2022). Dentre as principais fontes de matéria orgânica, destaca-se o esterco ovino, justificando-se por sua viabilidade na composição de substratos e elevada disponibilidade de aquisição (BORBOREMA et al, 2021;FARIAS et al, 2021), principalmente na microrregião do Cariri paraibano, onde a criação de ovinos é bastante pronunciada (OLIVEIRA et al, 2020). Com base no exposto, objetivou-se com este trabalho avaliar a demanda hídrica e o crescimento do feijão-caupi sob doses de esterco ovino na região do Cariri paraibano.…”
Section: Introductionunclassified
“…Os valores de pH não diferiram entre si e apresentaram faixa de variação semelhante à observada por outros autores, de 5,41 a 5,69 para Longissimus thoracis et lumborum de cordeiros após o estabelecimento do rigor mortis (Knight et al, 2019;Oliveira et al, 2019;Oliveira et al, 2020;Rant et al, 2019), mesmo após a maturação.…”
Section: Discussionunclassified
“…A perda de peso por cocção não diferiu entre as diferentes amostras de lombo (p ≤ 0,05), assim como em outros resultados obtidos em estudos com a raça Santa Inês, de 20 a 25% (Oliveira et al, 2010;Oliveira et al al., 2019). No entanto, esses resultados são inferiores aos apresentados por Bressan et al (2001), cerca de 29% para Longissimus dorsi de Santa Inês e Bergamácia e por Oliveira et al (2020), próximo a 40% para Santa Inês. Isso pode estar relacionado a diferenças de genótipo, idade e peso de abate dos animais, manejo pré e pósabate, tipo de equipamento utilizado nas análises, temperatura e tempo de cocção.…”
Section: Discussionunclassified
See 1 more Smart Citation